Pengaruh Teman Sebaya terhadap Pembelian Impulsif dengan Mediasi Kecemasan Finansial pada Mahasiswa Pengguna E-commerce atau Media Sosial di Kabupaten Paser - Istiqomah Istiqomah; Ibnu Khayath Farisanu (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study examines the influence of peer groups on impulsive buying, with financial anxiety as a mediator among college students using e-commerce or social media in Paser Regency. A quantitative cross-sectional design was employed and analysed using PLS-SEM with SmartPLS. The sample consisted of 282 active students selected through purposive sampling. Three reflective constructs were measured using a 5-point Likert scale: peer influence (8 items), financial anxiety (8 items), and impulsive buying (9 items). The measurement model assessment confirmed adequate convergent and discriminant validity (AVE = 0.545–0.715; Cronbach’s alpha = 0.883–0.954; Composite Reliability = 0.905–0.957; HTMT < 0.25). The structural model results showed that H1 was supported, indicating that peer influence had a significant positive effect on financial anxiety (β = 0.252; T = 4.036; p < 0.001). However, H2 was not supported, as financial anxiety had no significant effect on impulsive buying (β = 0.069; T = 0.815; p = 0.415). H3 was also not supported, showing that peer influence had no significant direct effect on impulsive buying (β = −0.007; T = 0.076; p = 0.939). Furthermore, H4 was not supported, indicating that financial anxiety did not mediate the influence of peer groups on impulsive buying (indirect effect = 0.017). These findings suggest that, in the context of students in remote areas, the hypothesised SOR mechanism does not operate fully: peer pressure triggers financial anxiety, but this anxiety does not translate into impulsive buying.